Global Demographic Trends, Capital Mobility, Saving and Consumption in Latin America and the Caribbean (LAC) - Orazio Attanasio; Andrea Bonfatti; Sagiri Kitao; Guglielmo Weber (Inter-American Development Bank (IDB), 2015)
This paper studies the effect of demographic transitions on the economy of Latin America and the Caribbean (LAC). The paper builds a model of multi-regions of the world and derives the path of macroeconomic variables including aggregate output, capital, labor and the saving rate as economies face a rapid shift in demographics. The timing and the extent of the demographic transition differ across regions. The model is simulated under both closed economy and open economy assumptions to quantify the roles played by factor mobility across regions in shaping capital accumulation and equilibrium factor prices.
hdl:11319/6945
Keywords: E21; F21; F41; J11; 330; Capital flows; Demographic trends; Latin America and the Caribbean (LAC)